An Analysis of the Potential Relationship of Triglyceride Glucose and Body Mass Index With Stroke Prognosis - Hou, Zongyi; Pan, Yuesong; Yang, Yindong; Yang, Xiaofan; Xiang, Xianglong; Wang, Yilong; Li, Zixiao; Zhao, Xingquan; Li, Hao; Meng, Xia; Wang, Yongjun (Frontiers in Neurology, 2021)
Background: The inverse association between obesity and outcome in stroke patients (known as the obesity paradox) has been widely reported, yet mechanistic details explaining the paradox are limited. The triglyceride glucose (TYG) index has been proposed as a marker of insulin resistance. We sought to explore possible associations of the TYG index, body mass index (BMI), and stroke outcome. Methods: We identified 12964 ischemic stroke patients without a history of diabetes mellitus from the China National Stroke Registry and classified patients as either low/normal weight, defined as a BMI < 25kg/㎡, or overweight/obese, defined as a BMI ≥ 25kg/㎡. We calculated TYG index and based on which the patients were divided into four groups. A Cox or logistic regression model was used to evaluate the association between BMI and TYG index and its influence on stroke outcomes, including stroke recurrence all-cause mortality and poor outcome (modified Rankin Scale score of 3 to 6) at 12 months. Results: Among the patients, 63.3% were male, and 36.7% were female, and the mean age of the patient cohort was 64.8 years old. The median TYG index was 8.62 (interquartile range, 8.25–9.05). After adjusting for multiple potential covariates, the all-cause mortality of overweight/obese patients was significantly lower than that of the low/normal weight patients (6.17% vs 9.32%; adjusted hazard ratio, 0.847; 95% CI 0.732-0.981). The difference in mortality in overweight/obese and low/normal weight patients with ischemic stroke was not associated with TYG index, and no association between BMI and TYG index was found. Conclusion: Overweight/obese patients with ischemic stroke have better survival than patients with low/normal weight. The association of BMI and stroke outcome is not changed by TYG index.